Measurement of the inclusive jet cross section at the Fermilab Tevatron pp̄ collider using a cone-based jet algorithm - Aaltonen, T; Adelman, J; Akimoto, T; Albrow, MG; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; et al. (2008)
We present a measurement of the inclusive jet cross section in pp̄ collisions at s=1.96TeV based on data collected by the CDF II detector with an integrated luminosity of 1.13fb-1. The measurement was made using the cone-based midpoint jet clustering algorithm in the rapidity region of |y|<2.1. The results are consistent with next-to-leading-order perturbative QCD predictions based on recent parton distribution functions (PDFs), and are expected to provide increased precision in PDFs at high parton momentum fraction x. The results are also compared to the recent inclusive jet cross section measurement using the kT jet clustering algorithm, and we find that the ratio of the cross sections measured with the two algorithms is in agreement with theoretical expectations over a large range of jet transverse momentum and rapidity. © 2008 The American Physical Society.